Comparison Between the Effect of Low-Energy Laser Application and Piezocision on Acceleration of Orthodontic Tooth Movement - Al Sherbiny, Ahmad Helal; Refai, Wael Mohamed Mubarak; Mohamed, Kareem M.; Elhiny, Omnia A.; Nasef, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
ABSTRACT the aim of the study was to study the effectiveness of Low Energy Laser Application or piezocisions in accelerating tooth movement, during canine retraction, compared to conventional canine retraction. Patients and Methods: A split mouth study design was done with two groups A and B. Each group confined 10 patients; in each patient one side was used as a control side and the contralateral side received either low-level laser therapy (LLLT) (group A) or piezocisions (group B). The evaluation data was gathered by Intra-oral measurements directly, every 2 weeks, over a 3 months retraction period. Results: Statistical analysis using Repeated measure ANOVA test was used to compare between more than two groups in related samples. Paired sample t-test was used to compare between two groups in related samples. Independent sample t-test was used to compare between two groups in non-related samples. direct intra-oral measurements from Group A illustrated that there was a statistically significant difference between the study and control sides (p<0.001) a total of 4.19 ± 0.5 mm canine retraction has been achieved in the low-level laser therapy (LLLT) assisted canine retraction side versus a 2.83 ± 0.2 mm total canine retraction in the control side. which was statistically significant. Group B illustrated that there was a statistically significant difference between the study and control sides ( p<0.001) that a total of 3.65± 0.4 mm canine retraction has been achieved in the piezocisions assisted canine retraction side versus a 2.79± 0.2 mm total canine retraction in the control side which was a highly statistically significant difference Conclusion: low-level laser therapy (LLLT) and Piezocisions techniques accelerated the rate of canine retraction during orthodontic treatment, with the low-level laser therapy (LLLT) being slightly more effective.